Low metallic wear of dynamic intraligamentary stabilization. (May 2017) - May, Christian; Gueorguiev, Boyko; Heuberger, Roman; Sague, Jorge; Gross, Christoph; Henle, Philipp; Delfosse, Daniel; Häberli, Janosch
Abstract: Dynamic Intraligamentary Stabilization (DIS) represents a treatment option for acute anterior cruciate ligament ruptures. The device used for DIS consists of a polyethylene braid and a metallic spring system, allowing the remnants of the ligament to recombine in a stabilized position over the self-healing period. This work addresses the metallic wear generated thereby. A cadaveric study was carried out with n=8 knees over 50'000 cycles, along with a control group to validate the cleaning and assembly process. Gravimetric analysis yielded a total wear of (0.28±0.35)mg for the entire implant. 50% of the wear originated from the bush and 46% from the clamping element. In a worst case scenario, a total wear of 1.7 mg would result during the functional lifetime. Abstract : Highlights: Dynamic Intraligamentary Stabilization generates 0.28 mg of wear over 50'000 cycles. Wear originates 50% from the bush and 46% from the clamping element. Wear generation takes place during regular operation, not assembly or disassembly. In a worst case scenario, a total wear of 1.7 mg results during the functional lifetime.